The challenge of strategic communication in higher education institutions: a study of the role of communication in promoting their social mission - Silva, Sónia Melo (2016)
Universities represent places of culture and knowledge, of which is expected commitment with societydevelopment. These institutions have been trying to give answer to the demands and challenges constantly presented to them and intensified by their commitment with social responsibility. In another instance it has been perceived that strategic communication, as tool oriented for the fulfillment of goals and objectives, has conquered an important place in these institutions. It is precisely in the center of strategic communication and social responsibility has relevant processes to universities that this study aims to focus on. It is intended to debate the relevance of strategic communication in the execution and divulgation of the mission of these institutions, particularly with regard of their role as important social agents. Therefore, it is wished to understand and discuss the relation of interdependence between the notions of strategic communication and social responsibility, supposing that the first is decisive for the success of the second. The conclusions of this brief study suggest that communicationactivities are extremely relevant for the fulfillment and divulgation of the social responsibility of universities, which is a fundamental part of their mission.